2020
DOI: 10.1080/01431161.2019.1711245
|View full text |Cite
|
Sign up to set email alerts
|

Reconstructing past forest composition and abundance by using archived Landsat and national forest inventory data

Abstract: Reconstructing past forest composition and abundance by using archived Reconstructing past forest composition and abundance by using archived Landsat and national forest inventory data Landsat and national forest inventory data

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 88 publications
(177 reference statements)
0
4
0
Order By: Relevance
“…In brief, forest composition was derived from Thapa et al. (2020) to represent the relative basal area (reported as a percentage of the total basal area) for both preferred and the full host complement for each respective defoliator, measured at two time periods (1985 and 2005). Four land cover structure variables (area‐weighted mean non‐forest patch size (ha), Shannon index of forest cover diversity, percent forest, and forest edge density (m/ha)) were derived from a time‐series of land cover maps (Wolter et al., 2012), averaged across the time period 1975–2000.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In brief, forest composition was derived from Thapa et al. (2020) to represent the relative basal area (reported as a percentage of the total basal area) for both preferred and the full host complement for each respective defoliator, measured at two time periods (1985 and 2005). Four land cover structure variables (area‐weighted mean non‐forest patch size (ha), Shannon index of forest cover diversity, percent forest, and forest edge density (m/ha)) were derived from a time‐series of land cover maps (Wolter et al., 2012), averaged across the time period 1975–2000.…”
Section: Methodsmentioning
confidence: 99%
“…Independent variables consisted of both forest composition and land cover structure variables. In brief, forest composition was derived from Thapa et al (2020) to represent the relative basal area (reported as a percentage of the total basal area) for both preferred and the full host complement for each respective defoliator, measured at two time periods (1985 and 2005).…”
Section: Landscape Partitioningmentioning
confidence: 99%
“…In this calibration process, certain assumptions regarding both the spatial and biophysical accuracy of FIA field plot data as well as the allometry used to determine CBD were adopted (Keane et al 2006). With respect to FIA, recent work in Minnesota, USA, provides evidence to question some of the common assumptions regarding the combined use of Landsat and FIA for mapping biophysical forest structure information, especially spatial accuracy and suboptimal subplot design with regard to 30-m satellite sensor data (Thapa et al 2020). Regardless of the sources of mapping error, it is understood that the absolute accuracy of the LANDFIRE CBD data product varies regionally (Keane et al 2006;Scott 2008;Krasnow et al 2009) and should not replace locally derived fuel products if they exist at finer spatial scales (Keane et al 2006), which is the pretext for this research.…”
Section: Introductionmentioning
confidence: 99%
“…Of these systems, we expected GM defoliation to be most intuitive and readily mapped via satellite sensor data due to GM's generalist broadleaf diet . We anticipated SBW defoliation to be the most challenging to map using satellite sensor data due to the combination of host's canopy position, multi-year needle longevity, and tree species diversity within the study region (Bhattarai et al, 2020;Thapa et al, 2020). Given these two remote detection extremes, we posited that JPBW defoliation detection would represent intermediate difficulty due to unique biophysical conditions of the jack pine host, including high host concentration, dominant vertical canopy position, and relatively short needle longevity compared to SBW.…”
Section: Defoliating Insects Have Pronounced Effects On Forest Health...mentioning
confidence: 99%